Global Method Application Deret Dadu Alfabet Media Assisted in Efforts to Improve Reading Ability Beginning (Research on Class II Students SD Negeri Sikepan 2) - Husna Hafidzotunnissa’ (Prosiding University Research Colloquium, 2021)
This study aims to determine the improvement of pre-reading skills through theglobal method assisted by Deret Dadu Alfabet media in grade II students of SD NegeriSikepan 2.This study used Classroom Action Research (CAR) held in grade II SD NegeriSikepan 2 apply three cycles. Each Each cycle is followed by four stage, namely: (1)planning action, (2) implementation of actions, (3) action observation and (4) actionreflection. The subjects of this study were all grade II students of SD Negeri Sikepan 2totaling 12 student with 8 male student and 4 female student. Methods of data collectionin this study using a performance test sheet, pretest and posttest question, and observationsheet. Methods of data analysis in this study using quantitative data and qualitative data.The result of this research shows there is an increase in the activity of grade IIstudents from 42% to 83%, and an increase in the average initial reading ability of studentsfrom 63 to 88 with a mastery percentage of 42% to 83%, and each cycle is increasing. Basedon the result of this study, it can be concluded that the global method assisted by DeretDadu Alfabet media is effective in